Airline Ticket Reservation System For Kampala Executive Aviation. - Magezi, David (Kabale University, 2024)
This project's main objective was to design an Airline Reservation System application that would enable customers to search and book flights, packages, and hotels. The project was designed in PHP technology and consists of an SQL server that acts as the database for the project. My motivation for the project came from my enthusiasm and strong urge to learn PHP. The Airline Reservation System project mainly consists of two types of users. The customers who access the information provided by the website and the administrator who modifies and updates the information available on the website. All the data needed for the application is stored in the form of tables in the SQL server 2000. The report contains the details of all the tasks carried out during the entire software development life cycle of the Airline Reservation Project. This document depicts all the details of the project starting from the project design to testing.